Evaluasi Penerapan Internal Control dan Pelaksanaan Good Corporate Governance pada PT PLN (Persero) Distribusi Jakarta Raya dan Tangerang - Iswandi, Iswandi (Bina Nusantara University, 2011)
PT. PLN (Persero) Distribusi Jakarta Raya dan Tangerang have implemented Internal Control and Good Corporate Governance. The research would like to evaluate the implementation of Internal Control accordance with COSOâs criteria (Committee of Sponsoring Organizations of the Treadway Commission) and KNKGâs criteria (Komite Nasional Kebijakan Governance). Based on research found that five components of COSO such as control environment, risk assessment, control activities, information and communication, monitoring have been implemented but unfortunately one of theÂ componentÂ such as control activities not yet implemented properly accordance with COSOâs criteria. The company also have beenÂ imlementedÂ GCG accordance with KNKGâs criteria but still need development through internalization GCGâs spirit among the employees because some employees still have different perception related to GCG. ForÂ exampleÂ from employeeÂ stand pointÂ thereâs no problem receiveÂ specialÂ gift or receive special payment from customer and have a conflict of interest whenÂ dealÂ withÂ publicÂ accountant.